Exercise therapy and physical activity promotion: do exercise therapists assess or receive information on clients' relevant personal factors? A national survey from Germany. (2nd September 2020) - Geidl, Wolfgang; Deprins, Judith; Cassar, Samuel; Streber, René; Portenlänger, Florian; Sudeck, Gorden; Pfeifer, Klaus
Abstract: Background: Physical activity promotion requires a multi-layered assessment that does not only assess body functions but which in particular also includes the measurement of personal factors (e.g. exercise self-efficacy). Objectives: The purpose was to review the utilisation of standardised measurements (SMs), admission interviews and interdisciplinary information sharing, and to analyse the content of these practices with respect to physical activity promotion. Design: Observational, cross-sectional national survey. Method: A Germany-wide, quantitative survey, collecting information from 713 exercise therapy departments, was conducted. Measurements were classified as standardised or non-standardised and assigned to the International Classification of Functioning (ICF). Admission interviews and information from other professionals were analysed using a qualitative content analysis. Results: In total, 1008 SMs included 9007 ICF concepts: 16% were classified as personal factors, but none were clearly related to physical activity promotion. Admission interviews contained several non-standardised assessments of personal factors: goals (40%), exercise experiences/activity bibliography (10%), activity level (5%), exercise preferences (2%). Information sharing does not contain relevant information for physical activity promotion. Discussion: Exercise therapists have scant information about the personal factors that influence clients' physical activity behaviour. An assessment for physical activity promotion that includes physical functioning and personal factors has, so far, barely been implemented in practice.